Effects of NaCl stress on leaf physiology and photosynthetic indexes of four apple rootstocks - WANG Zhuli; JIN Xilige; LI Wensheng; ZHANG Ping (Guoshu xuebao)
[Objective] Soil salinity in apple orchards has become an escalating issue due to highly mineralized irrigation water and intense evaporation in Xinjiang of China. Selection of proper rootstock with reliable resistance to salinity is crucial issue for apple production. The effects of NaCl stress on leaf physiology and photosynthetic indexes of the 4 apple rootstocks was evaluated through pot experiment with the intension to select the rootstock with potential resistant to salinity. [Methods] The nursery trees of M7, G935, and M9T337 were propagated from cuttings, while those of Malus sieversii was propagated from sowing of seeds. All plants were transplanted in late March, 2023 at the experimental base on the campus of Xinjiang Agricultural University, potted in 23 cm × 28 cm plastic containers filled with a 4∶1 (V/V) mixture of peat soil and turf, with each pot containing 5 kg of substrate. The pots were placed on trays managed uniformly. The salt stress experiment began in late July, 2023, with NaCl solution concentrations at 0, 2, 4, 6, 8, and 10 g·L-1, where 0 g·L-1 served as the control group (CK). Nine plants per concentration gradient for each rootstock, were used, in the experiment and three plants constituted one biological replicate. The corresponding NaCl solutions were used for irrigation.800 mL of solution was applied daily per pot. Any leachate collected in the trays was poured back to the pots to prevent salt loss from the substrate. Three days later, all treatments reached the target salt concentrations, and the evaluation started. On day 0, all potted nursery trees were weighed for the first time, the weight included the pot, substrate, plant, and initial moisture in the substrate. Every four days, at the same time, the pots were reweighed and replenished with water to maintain consistent salt concentrations. The experiment continued for multiple cycles until significant phenotypic differences were observed among the rootstocks. [Results] With increase of NaCl concentrations and prolonged stress duration, the 4 rootstocks generally exhibited a decreasing trend in tree height increment and ground diameter increment of the trees. Additionally, as the stress intensity intensified, the trees displayed varying degrees of salt damage symptoms, such as leaf yellowing, scorching, and curling, with the most severe stress effects observed at NaCl concentrations of 8-10 g·L-1. Concurrently, the relative conductivity and MDA content of the 4 apple rootstocks showed an overall upward trend with the rise of salt concentrations and extended stress exposure, indicating that the plasma membranes of all the 4 rootstocks were damaged under varying salt stress conditions, with the severity of damage progressively worsening over time. Notably, the M. sieversii exhibited higher relative conductivity and MDA content compared with the other three rootstocks, with the largest increase relative to the control group by the end of the stress period, suggesting the most severe cell membrane damage among the tested materials. Under varying NaCl concentration stresses, prolonged exposure time ultimately led to significantly higher soluble protein and soluble sugar content in the four apple rootstocks compared with those of the control. Among them, M7 exhibited the highest soluble sugar content under different NaCl concentrations, indicating its superior stress resistance. The activities of SOD, POD, and CAT in the four rootstocks generally showed an initial increase followed by a decline. This suggests that under salt stress, the antioxidant capacity of all the four rootstocks was enhanced to scavenge excess reactive oxygen species and mitigate membrane damage. However, prolonged stress exceeded the tolerance threshold of the rootstock trees, reducing their ability to eliminate peroxide radicals and leading to metabolic imbalance, ultimately resulting in decreased enzyme activities. Notably, among the four rootstocks, M9T337 consistently exhibited lower antioxidant enzyme activity, indicating its weaker capacity to scavenge peroxide radicals under salt stress conditions. Under varying salt concentration stresses, all the four apple rootstocks showed a decreasing trend in chlorophyll content, with higher salt concentrations leading to more pronounced reductions. Compared with the other three rootstocks, G935 exhibited the smallest decline in chlorophyll content relative to its control across different salt concentrations while maintaining the highest absolute levels, demonstrating its superior ability to maintain relatively stable chlorophyll content under salt stress. The trends in stomatal conductance and transpiration rate were similar, indicating that stomatal limitation was the primary factor. However, between days 5-25, M. sieversii showed a decrease in stomatal conductance at 8-10 g·L-1 NaCl concentrations without a corresponding decline in intercellular CO2 concentration, which instead exhibited an upward trend, suggesting a gradual increase in nonstomatal limitations. Among the tested rootstocks, M7 displayed relatively smaller fluctuations in stomatal conductance, transpiration rate, and net photosynthetic rate, indicating better performance. By the end of the NaCl stress treatments, the water use efficiency of all rootstocks was lower than their respective CK groups, confirming cellular damage caused by the salt stress. Notably, the trees of G935 under salt treatment showed the greatest reduction in WUE compared with those of the CK, indicating it was the most severely affected by the stress conditions. [Conclusion] This study revealed significant morphological variations and differential salt tolerance among the four apple rootstocks under varying salt stress conditions. As salt concentration and stress duration increased, the nursery trees of the rootstocks exhibited significant decreases in the stomatal conductance, transpiration rate and net photosynthetic rate, while intercellular CO2 concentration showed an upward trend compared with those of the CK. The relative conductivity and malondialdehyde content demonstrated continuous accumulation, and the activities of SOD, POD and CAT initially increased before declining. Ultimately, salt stress significantly elevated the soluble protein and soluble sugar content in all four rootstocks relative to the CK. The principal component analysis identified five key evaluation indicators: chlorophyll content, transpiration rate, water use efficiency, SOD activity and intercellular CO2 concentration. The comprehensive evaluation of salt tolerance across different stress levels revealed the following ranking for the tolerance to salinity among the four rootstocks: M7>M. sieversii>G935>M9T337.